2010
DOI: 10.1073/pnas.1006338107
|View full text |Cite
|
Sign up to set email alerts
|

Hyper telomere recombination accelerates replicative senescence and may promote premature aging

Abstract: Werner syndrome and Bloom syndrome result from defects in the RecQ helicases Werner (WRN) and Bloom (BLM), respectively, and display premature aging phenotypes. Similarly, XFE progeroid syndrome results from defects in the ERCC1-XPF DNA repair endonuclease. To gain insight into the origin of cellular senescence and human aging, we analyzed the dependence of sister chromatid exchange (SCE) frequencies on location [i.e., genomic (G-SCE) vs. telomeric (T-SCE) DNA] in primary human fibroblasts deficient in WRN, BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 50 publications
(62 reference statements)
7
46
0
Order By: Relevance
“…BLM may be important in the progression of the replication fork globally, whereas WRN may play a more specific role in telomere replication. Supporting this concept, Bailey and colleagues (62) recently demonstrated that depletion of WRN induces T-SCE, whereas depletion of BLM induces SCE at non-telomeric chromosome regions (i.e. global SCE).…”
Section: Discussionmentioning
confidence: 94%
“…BLM may be important in the progression of the replication fork globally, whereas WRN may play a more specific role in telomere replication. Supporting this concept, Bailey and colleagues (62) recently demonstrated that depletion of WRN induces T-SCE, whereas depletion of BLM induces SCE at non-telomeric chromosome regions (i.e. global SCE).…”
Section: Discussionmentioning
confidence: 94%
“…53,54 Further, WRN-deficient cells undergo rapid replicative senescence without accelerated telomere shortening but with aberrant telomeric structures, including increased telomere associations and telomere sister chromatid exchanges and loss of the G-rich lagging strand DNA. 37,41 These data suggest that telomere dysfunction is one cause of the observed genomic instability and premature aging observed in WS. It is possible that the interaction of XPG with WRN is functionally important in telomere maintenance, and so it will be of interest to learn whether XPG has a role at telomeres in S phase.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 85%
“…37 Loss of WRN leads to increased chromosome aberrations, defective resolution of Holliday junctions, abnormal DNA replication intermediates, large deletions and increased incidence of telomere sister chromatid exchange. [37][38][39][40][41] Direct measurement of replication fork kinetics showed that, after DNA damage, replication fork progression was significantly slower in the absence of WRN.…”
Section: Resultsmentioning
confidence: 99%
“…iPSCs with haploinsufficiency of telomerase (Terc +/− ) show an increase in mean telomere length between P6 and P22, which coincides with increased heterogeneity (Supplementary information, Figure S3B), yet have much reduced expression levels of Dnmt3a, Dnmt3b and Suv39h2 ( 4B) at early passage and increased TSCE ( Figure 4A) at early-to-mid-passage, likely suggesting that recombination appears to be a response to the lack of active telomerase. However, excess telomere recombination by TSCE in telomerase-deficient cells also can cause accelerated cellular senescence [46]. Aberrant frequent telomere sister chromatid recombination, telomere loss and instability, together with insufficient reprogramming of iPSCs due to telomerase deficiency and abnormal epigenetic changes eventually lead to cell senescence as seen in Terc −/− iPSCs at late passages.…”
Section: Discussionmentioning
confidence: 99%